Comics Activism: An Interview with Comics Artist and Activist Kate Evans - Dominic Davies (The Comics Grid: Journal of Comics Scholarship, 2017)
This is an interview with comics artist Kate Evans, author of Red Rosa (2015) and Threads: From the Refugee Experience (2017), as well as a number of other comics, about her recent work, which operates at the intersection of several of the most exciting genre developments in comics in recent years. In the interview Evans reflects on recent shifts in comics journalism, as well as other trends in the field such as the rise of graphic memoir, through examples taken from Evans’s own work as well as that of Joe Sacco, Lynda Barry, Alison Bechdel and others.